Empiric Therapy with BRAF and MEK Inhibitors in Metastatic Melanoma. (18th June 2019) - Cann, Christopher G.; Tillman, Benjamin F.; Davis, Elizabeth J.; Johnson, Douglas B.
Abstract: BRAF and MEK inhibitors are highly active in the setting of BRAF V600 mutant melanoma. Rarely, patients without previous testing present with fulminant progression necessitating emergent treatment prior to BRAF testing results. The safety and efficacy of empiric treatment in this setting is unclear. Herein, we present two patients treated with empiric BRAF and MEK inhibitors, resulting in dramatic clinical improvement in one patient later found to have a BRAF mutation, and lack of improvement (but no accelerated progression) in a patient lacking this mutation. Empiric BRAF and MEK inhibitor treatment should not be routinely pursued but may be given safely in rare, emergent situations. Abstract : This brief communication presents case reports for two patients with metastatic melanoma treated empirically with BRAF and MEK inhibitors.